'Our Lives' and 'Life Happens', from stigma to empathy in young people's depictions of sexual health and relationships. (1st April 2018) - Senior, Kate; Grozdanovski, Laura; Chenhall, Richard; Minton, Stephen
This article describes qualitative research undertaken to explore young people's understanding of sex and relationships that used a scenario-driven body-mapping technique. This art-based method was designed to allow young people to think deeply about the subject and build upon each other's ideas through the medium of decorating a life-sized human body. Although this method produced rich information the depictions of young people tended to be highly stigmatized. We further refined the method to encourage young people to empathize with the character that they created and the resultant research became the basis for the sexual health resource 'Life Happens'.